Is color vision deficiency an advantage under scotopic conditions? - Simunovic, M; Regan, B; Mollon, J (2001)
PURPOSE: To examine experimentally whether color vision deficiency confers a selective advantage under scotopic conditions. METHODS: Red-green color-deficient subjects, monochromats, and age-matched color-normal control subjects were examined. In each subject the time course of dark adaptation, scotopic visual field sensitivity, and performance on a scotopic perceptual task were measured. RESULTS: No significant differences were found between red-green color-deficient subjects and control subjects on any of the three tests. Our small sample of monochromats had higher absolute thresholds than the corresponding control subjects, but their performance at the scotopic visual field test and perceptual task did not differ significantly from that of color-normal subjects. CONCLUSIONS: No evidence was found that red-green color deficiency or monochromatism confers a selective advantage under scotopic conditions.